Managing Alzheimer's Dementia with Homecare in an African American Family During the COVID Pandemic. (December 2022) - Eversley, Rani; Favila, Wendy; Jenkins, Sharon Rae; Godwin, Makula; Pedrosa, Maria
In the US, over 95 million people have been infected with COVID and over 1 million have died. 10% of Californians are infected with COVID with higher rates reported among Latinx, Pacific Islanders, and low-income people. Higher death rates have been reported among African Americans. People living with Alzheimer's Disease (AD) are also more likely to be infected with COVID. African Americans with AD have three times the COVID rate of Whites. Homecare workers who care for moderate to severe AD in home and community settings are frontline essential workers who manage complex AD-related problems like incontinence. Little is known about communication and problem-solving processes between homecare workers and families of people with AD to manage continence at home. This report describes the challenges facing homecare workers illustrated by an African American family caring for a relative with advanced AD during pandemic.